Instill Character Education During Online Learning with Developing Whiteboard Animation Proclamation-Based - Medita Ayu Wulandari; Zaqiyah Lailatul Farihah; Asep Samsudin; Uus Kuswendi (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2022)
Learning activities during pandemics present new challenges in Indonesian education, especially in applying character education in elementary schools. This study aims to develop appropriate and effective learning media to instill character education during online learning. The learning media developed is in the form of whiteboard animation proclamation-based. This development consists of nine stages of development of Dick and Carey. Research data was obtained through observation,interviews, and questionnaires. The feasibility of the Whiteboard Animation Proclamation-Based results was obtained through a product assessment questionnaire from a material expert, a media expert, a language expert, and classroom teachers. Meanwhile, the test results were obtained from a responsequestionnaire to 50 fourth-grade students in Cimahi. The validation results show that the Whiteboard Animation Proclamation-Based is feasible from assessing the material aspect with an average of 4.45. The media aspect is also considered very feasible with an average of 4.67, and the language aspect is feasible with an average of 4.54. The results obtained from practitioners also get very decent criteria with an average of 4.67. The results of small and large-scale trials received an average of 100% with very good criteria. This development concludes that the Proclamation-Based Whiteboard Animation developed is very good enough to be used as a learning media to support online learning in elementary schools.